Microstructural study of heat treated chromium alloyed grey cast iron (2010)
"This work investigated the effect of annealing, normalizing and quenching heat treatments on the microstructure of some chromium alloyed grey cast iron. Three sets of ten samples each having chromium contents of 0.5, 1.5 and 2.5% were heat treated above the upper critical temperature, to austenitizing temperatures (800oC, 850oC, 900oC) for one hour each and then annealed, normalized and water quenched. Metallographic analyses of the heat treated samples were done. The results showed carbides content increased with increasing Chromium addition. "